Overview of the atmospheric research activities and results at Pallas GAW station - Hatakka, J.; Aalto, T.; Aaltonen, V.; Aurela, M.; Hakola, H.; Komppula, M.; Laurila, T.; Lihavainen, H.; Paatero, J.; Salminen, K.; Viisanen, Y. (Boreal Environment Research Publishing Board, 2024)
Finnish Meteorological Institute's air quality measuring station at Pallas, in northern Finland, has been part of the Global Atmosphere Watch programme of the World Meteorological Organization since 1994. Tropospheric air composition and meteorological measurements are made at four different locations. Measured components include greenhouse and reactive gases, volatile organic compounds, chemistry of precipitation and aerosols, radon, carbon dioxide flux, meteorological parameters and a number of different aerosol characteristics. Pallas has proven to be a good site for measuring continental background air. This paper gives a general overview of the Pallas GAW station measurement sites and methods, and extensive overview of the scientific results.